Pandangan Bisnis Syariah Terhadap Perkembangan Financial Technology (Study Kasus Fitur Serbu Seru dalam Aplikasi Bukalapak) - Annas Syams Rizal Fahmi; Devid Frastiawan Amir Sup; Muhammad Irkham Firdaus; Fadhila Sukur Indra; Meitria Cahyani (Proceedings Series on Social Sciences & Humanities, 2022)
The phenomenon of buying and selling online through various features that place lower prices attracts buyers. The low price outside the normal price makes the people who see it interested in joining the program on Bukalapak's exciting attack feature. There is a lack of clarity in the terms of the contract and its implementation in the purchase of an item in the Bukalapak attack feature, it is stated that the initial contract is a sale and purchase contract but the item is drawn to get the winner of the item. So it is necessary to conduct research to discuss the analysis of the contract on this transaction. This study aims to determine the contract used for the online buying and selling transaction model of the Bukalapak attack feature. This research is qualitative in nature, with a descriptive analytical approach. This type of research is a library (library research) with the method of textbook analysis and literature study. The results of this study indicate that the pillars of buying and selling have fulfilled the elements in the sale and purchase contract. However, there are defects in the Kabul agreement, namely different payment times, the delivery of goods to buyers is not on time. The time is different because the sale and purchase agreement was originally a unidan system so buyers were randomly selected.